(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT: This article examines the extent to which corrupt practices in electoral processes in Africa have hindered realisation of human rights generally and the right to vote in free and fair elections specifically. It demonstrates that corruption has had a deleterious effect on enjoyment of socio-economic rights, civil and political rights. The authors posit that there is an established pattern of widespread voter bribery, misuse of state resources and absence of effective regulations on campaign and political party financing in many African countries. The net effect of this pattern has been to render the genuineness of most elections questionable and free expression of the will of electors doubtful. The authors propose, inter alia, that African judiciaries should abandon their fixation with quantitative assessments in electoral disputes where mathematical questions of whether there is a clear ‘winner’ take precedence. This, at the expense of failure to interrogate the qualitative aspects of electoral processes and which interrogation would invalidate electoral outcomes tainted by corruption. To demonstrate commitment to safeguarding the right to vote in free and fair elections, we argue that political and judicial organs of the AU should understand corruption in electoral processes as attempts at unconstitutional change of government or retention of power. TITRE ET RÉSUMÉ EN FRANCAIS: Corruption et le droit de vote dans élections libres et équitables en Afrique: la volonté du peuple à vendre RÉSUMÉ: Cet article examine la mesure dans laquelle la corruption dans les processus électoraux en Afrique a entravé la réalisation des droits de l’homme en général et du droit de vote lors d’élections libres et équitables en particulier. L’article démontre que la corruption a eu un effet préjudiciable sur la jouissance des droits socioéconomiques, civils et politiques. Les auteurs estiment qu’il existe un schéma établi de corruption généralisée, d’utilisation abusive des ressources de l’État et d’absence de réglementation efficace sur le financement des campagnes et des partis politiques dans de nombreux pays africains. Ce schéma a mis en doute la sincérité de la plupart des élections. Il a également remise en question la libre expression de la volonté de l’électeur. Les auteurs proposent, entre autres, que les cours et tribunaux africains abandonnent leur fixation sur les évaluations quantitatives lors des contentieux électoraux où la question mathématique qui prime est celle de savoir si un « gagnant » se dégage clairement. Ceci, au détriment de l’échec de l’examen des aspects qualitatifs des processus électoraux qui pourrait conduire à l’invalidation des résultats électoraux dont le processus a été entaché d’actes de corruption. Afin de démontrer leur volonté de préserver le droit de vote lors d’élections libres et équitables, nous soutenons que les organes politiques et judiciaires de l’Union africaine doivent comprendre la corruption dans les processus électoraux comme une tentative de changement anticonstitutionnel de gouvernement ou de maintien du pouvoir.